2002
DOI: 10.1002/hc.10046
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of sterically congested 1,6‐ and 1,7‐bis(diazo)alkanes with elemental sulfur and selenium: Formation of cyclohexene, 1,2‐dithiocane, 1,2‐diselenocane, and 1,2,3‐triselenecane derivatives

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…
Four-membered ring [PhP(Se)(l-Se)] 2 (Woollins' reagent, WR) reacts with disodium alkenyl-diols followed by in situ ring-closure reaction with appropriate dibromoalkanes affording a series of unusual nineto fifteen-membered organoselenophosphorus macrocycles bearingThe synthesis of macrocycles containing heavier elements is challenging and hetero-macrocycles are very rare 1 thus organoselenium heterocycles containing more than eight-membered rings with at least two selenium atoms are limited. [2][3][4][5][6][7] The known methods to prepare these heterocyclic compounds in general suffer from the use of highly toxic reagents with harsh reaction conditions, low yields or multi-steps. We, and others, have developed and exploited the chemistry of 2,4-bis(phenyl)-1,3-diselenadiphosphetane-2,4-diselenide (Woollins' reagent, WR) as a versatile selenation reagent in synthetic chemistry.
…”
mentioning
confidence: 99%
“…
Four-membered ring [PhP(Se)(l-Se)] 2 (Woollins' reagent, WR) reacts with disodium alkenyl-diols followed by in situ ring-closure reaction with appropriate dibromoalkanes affording a series of unusual nineto fifteen-membered organoselenophosphorus macrocycles bearingThe synthesis of macrocycles containing heavier elements is challenging and hetero-macrocycles are very rare 1 thus organoselenium heterocycles containing more than eight-membered rings with at least two selenium atoms are limited. [2][3][4][5][6][7] The known methods to prepare these heterocyclic compounds in general suffer from the use of highly toxic reagents with harsh reaction conditions, low yields or multi-steps. We, and others, have developed and exploited the chemistry of 2,4-bis(phenyl)-1,3-diselenadiphosphetane-2,4-diselenide (Woollins' reagent, WR) as a versatile selenation reagent in synthetic chemistry.
…”
mentioning
confidence: 99%
“…The reaction of bis(diazo)octamethyldecane 100 with elemental selenium in DBU at 130 • C yielded 1,2-di-tert-butyl-3,3,6,6-tetramethylcyclohexene 101 as the major product along with trans-3,8-di-tert-butyl-4,4,7,7-tetramethyl-1,2-diselenocane 102, while the analogous reaction of the reagent 100 with elemental sulfur in DBU resulted in trans-3,8-di-tert-butyl-4,4,7,7-tetramethyl-1,2-dithiocane 103 as the only product [106] (Scheme 40). The reaction of 3,9-bis(diazo)-2,2,4,4,8,8,10,10-octamethylundecane 104 with elemental selenium in DBU at 80 • C resulted in the formation of cyclic triselenide, cis-4,10-di-tert-butyl-5,5,9,9-tetramethyl-1,2,3-triselenecane 105 as the only identifiable product [106] (Scheme 40). The structures of the heterocycles 103 and 105 were confirmed by X-ray crystallography.…”
Section: Formation Of Heterocycles Via Cyclization Of Diazo-compounds...mentioning
confidence: 99%
“…The reaction of sterically congested 3,8‐bis ‐ diazodecane 176 with elemental sulfur activated by DBU at 130 °C gave dithiocane 177 (77%) as a single isomer (Scheme ) . This result is remarkable since it was previously reported that the reactions of diaryldiazomethane with elemental sulfur at room temperature are synthetically useful to prepare episulfides…”
Section: Sulfur As Building Block – Sulfuration Reactionsmentioning
confidence: 99%